Characterization of melanoidin formed from glucose with alanine by Fluorescence spectroscopy and redox chemistry in vitro cells - Mohsin, Ghassan Faisal; Jaafar, Abdulridha Ati (Journal of natural sciences, life and applied sciences, 2020)
Possible identify and describe a polymer formed from Glc with Ala by Fluorescence spectroscopy. Melanoidins before dialysis was higher than those of melanoidin after dialysis. Time‐resolved fluorescence has been applied in the characterization of melanoidin and was observed. Melanoidins show a decrease in the absorption after the addition of hydrogen peroxide when the concentrations of H2O2 from 100 - 200 μl are used. However, the data suggests that the melanoidin did not penetrate into the cells (CHO-K1) after 1 and 2 hours, but it can be observed after 24 hours.Abbreviation: TRES, time-resolved emission spectra ; Glc, Glucose ; Ala, Alanine ; YFP, Yellow fluorescence protein ; GFP, green fluorescence protein ; CHO, Chinese hamster ovary
Keywords: melanoidin; fluorescence spectroscopy; hydrogen peroxide; cells